2020
DOI: 10.3390/e22121380
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Decline in Alzheimer’s Disease Is Detected by Complexity Analysis of Multimodal EEG-fNIRS

Abstract: Alzheimer’s disease (AD) is characterized by working memory (WM) failures that can be assessed at early stages through administering clinical tests. Ecological neuroimaging, such as Electroencephalography (EEG) and functional Near Infrared Spectroscopy (fNIRS), may be employed during these tests to support AD early diagnosis within clinical settings. Multimodal EEG-fNIRS could measure brain activity along with neurovascular coupling (NC) and detect their modifications associated with AD. Data analysis procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Alzheimer's disease, the most common cause of dementia or neurocognitive disorder, can cause functional disruptions of speech, orientation, and memory (Alzheimer’s Association [AA], 2021; Perpetuini et al, 2020). OADWS often exhibit similarly disorganized or incoherent speech, as well as difficulties in memory and orientation (APA, 2013).…”
Section: Holistic Adaptation Of Accepted Communication Interventions ...mentioning
confidence: 99%
“…Alzheimer's disease, the most common cause of dementia or neurocognitive disorder, can cause functional disruptions of speech, orientation, and memory (Alzheimer’s Association [AA], 2021; Perpetuini et al, 2020). OADWS often exhibit similarly disorganized or incoherent speech, as well as difficulties in memory and orientation (APA, 2013).…”
Section: Holistic Adaptation Of Accepted Communication Interventions ...mentioning
confidence: 99%
“…This theory postulates that, as stated by Goldberger et al 24 : 1) "the output of healthy systems (...) reveals a type of complex variability associated with long-range correlations", and 2) "this type of multiscale, nonlinear complexity breaks down with aging and disease, reducing the adaptive capabilities of the individual". Recent evidence seems to support this theory as, for instance, entropy measures of cerebral blood flow velocity decayed in altered states 27 , actigraphy data exhibited lower complexity in depressed subjects as compared to non-depressed controls 28 , and complexity of EEG signals from subjects with AD correlated well with performance in working memory tasks 29 . MSE analysis can have significant implications in biomedical research as several studies have demonstrated its application to detection of heartbeat irregularity 22,30 , postural control alterations 31 and postoperative neurocognitive dysfunction 32 , and diagnosis of depression 28 , Parkinson's disease 33 , schizophrenia 34 , and AD 35 .…”
Section: Introductionmentioning
confidence: 95%
“…Because of the absence of electro-optical interference with these two scalp-located technologies, it is simple to integrate fNIRS with EEG. The simplicity of the hardware integration also encourages the development of unified analytical frameworks [19,47,48]. EEG is a well-established technique in neurological and neuroimaging settings suitable for capturing the temporal dynamics of brain electrical activity through measurements of voltages generated by macroscopic currents within neuronal ensembles [49].…”
Section: Introductionmentioning
confidence: 99%